Investigation of the role of rare TREM2 variants in frontotemporal dementia subtypes - Thelen, Mathias; Razquin, Cristina; Hernandez, Isabel; Gorostidi, Ana; Sanchez-Valle, Raquel; Ortega-Cubero, Sara; Wolfsgruber, Steffen; Drichel, Dmitriy; Fliessbach, Klaus; Duenkel, Tanja; Damian, Marinella; Heilmann, Stefanie; et al. (Neurobiology of Aging, 2014)
Frontotemporal dementia (FTD) is a clinically and genetically heterogeneous disorder. Rare TREM2 variants have been recently identified in families affected by FTD-like phenotype. However, genetic studies of the role of rare TREM2 variants in FTD have generated conflicting results possibly because of difficulties on diagnostic accuracy. The aim of the present study was to investigate associations between rare TREM2 variants and specific FTD subtypes (FTD-S). The entire coding sequence of TREM2 was sequenced in FTD-S patients of Spanish (n = 539) and German (n = 63) origin. Genetic association was calculated using Fisher exact test. The minor allele frequency for controls was derived from in-house genotyping data and publicly available databases. Seven previously reported rare coding variants (p.A28V, p.W44X, p.R47H, p.R62H, p.T66M, p.T96K, and p.L211P) and 1 novel missense variant (p.A105T) were identified. The p.R47H variant was found in 4 patients with FTD-S. Two of these patients showed cerebrospinal fluid pattern of amyloid beta, tau, and phosphorylated-tau suggesting underlying Alzheimer's disease (AD) pathology. No association was found between p.R47H and FTD-S. A genetic association was found between p.T96K and FTD-S (p = 0.013, odds ratio = 4.23, 95% Confidence Interval [1.17-14.77]). All 6 p.T96K patients also carried the TREM2 variant p.L211P, suggesting linkage disequilibrium. The remaining TREM2 variants were found in 1 patient, respectively, and were absent in controls. The present findings provide evidence that p.T96K is associated with FTD-S and that p.L211P may contribute to its pathogenic effect. The data also suggest that p.R47H is associated with an FTD phenotype that is characterized by the presence of underlying AD pathology.
EVALuna2:23660